Intellivent: A Business Intelligence Platform for Event Management Using Gamified Mobile Application and QR Code - Adiputra, Wilbert; Purnama, James; Anthony, Randy (Swiss German University, 2017)
One way for a company to communicate to their customer and promote their products is by participating or holding an event, like an exhibition or a seminar. For the event holder and organizer, it will be their best interest to gat her as much data as they can, however for now some of the company may find it hard to find those data. From the visitor perspective, there may be less incentive on the user to interact and engage more in an event. Intellivent is a platform for event manage ment, which features a gamification using gamified QR code. The gamification can be used as a tool for the event organizer to obtain more data regarding on activity in an event, and the visitor will be rewarded when they engage more in an event. A prototyp e has been created and tested on Islamic Book Fair 2019 where it is downloaded by 2000 users from the Play Store. Another version is created to be used in SGU Open House and Patjar Merah Malang 2019, a book bazaar that is predicted to gross around 5 Billion Rupiah. The implementation of the first prototype receive a very positive result from both the Event Organizer and the visitor of the event.